Psychotherapeutic actions to develop social skills in a group of patients treated in two centers for human development in Peru - Pérez Martinto, Pedro Carlos (2024)
This scientific article is part of the research-related results within the Life Sciences and Human Health Care research line. These investigations made it possible to implement a group of actions within a strategy aimed at developing social skills in a group of adolescents and a group of patients with autism spectrum disorders (ASD) who were diagnosed. To this end, we analyzed the populations of 220 adolescents attended by a Health Center, and of 262 patients with autism spectrum disorders, from the Equine Therapy Center. An intentional sample was selected, meeting an inclusive criteria group of 132 adolescents and 61 patients with ASD. The most relevant results were obtained; from the application of the instrument was the manual of social skills and the scale of Scale of assessment of social competence; It is possible to characterize the current state of the subjects and develop a group of actions for their treatment. Its application led to greater relaxation and muscle elongation for better muscle coordination by synchronizing the neuronal structure with new movement patterns; as well as better assertiveness, communication, decision-making and self-esteem.